2019
DOI: 10.1029/2018ea000546
|View full text |Cite
|
Sign up to set email alerts
|

Validity Study of the Swarm Horizontal Cross‐Track Ion Drift Velocities in the High‐Latitude Ionosphere

Abstract: High‐latitude ionospheric plasma convection plays a fundamental role in determining many processes in the terrestrial ionosphere. Electric Field Instruments on the European Space Agency's three polar‐orbiting Swarm satellites measure ionospheric ion drift velocities at about 500 km altitude using thermal ion imager energy/angle‐of‐arrival electrostatic analyzers. Recently, European Space Agency released horizontal cross‐track components of these drifts, calibrated at high latitudes. This paper concerns the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 52 publications
3
55
0
Order By: Relevance
“…The measurements from the satellites are well suited for the study of ionospheric subauroral phenomena. While a direct intersatellite comparison has not been done for the Swarm satellites, scientific publications using multiple Swarm satellites (Archer et al, 2015;Goodwin et al, 2015;Spicher et al, 2015) as well as validation studies (Lomidze et al, 2017(Lomidze et al, , 2019 all show the Swarm satellites to behave similarly to one another. The Swarm satellites measure electric and magnetic fields, as well as electron density and temperature; see Jørgensen et al (2008) and Knudsen et al (2017) for more information on the Swarm instrument package.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements from the satellites are well suited for the study of ionospheric subauroral phenomena. While a direct intersatellite comparison has not been done for the Swarm satellites, scientific publications using multiple Swarm satellites (Archer et al, 2015;Goodwin et al, 2015;Spicher et al, 2015) as well as validation studies (Lomidze et al, 2017(Lomidze et al, , 2019 all show the Swarm satellites to behave similarly to one another. The Swarm satellites measure electric and magnetic fields, as well as electron density and temperature; see Jørgensen et al (2008) and Knudsen et al (2017) for more information on the Swarm instrument package.…”
Section: Methodsmentioning
confidence: 99%
“…In this study we present measurements from all three Swarm satellites, which implies that the satellites are all calibrated to one another. While a direct intersatellite comparison has not been done for the Swarm satellites, scientific publications using multiple Swarm satellites (Archer et al, 2015;Goodwin et al, 2015;Spicher et al, 2015) as well as validation studies (Lomidze et al, 2017(Lomidze et al, , 2019 all show the Swarm satellites to behave similarly to one another.…”
Section: 1029/2019gl082687mentioning
confidence: 99%
“…The entire cross‐track ion drift data (Viy, in the horizontal direction perpendicular to the satellite orbit) from November 2015 to December 2017 are used. In order to get more usable ion drift data, the recalibration of data was carried out by setting the velocity to zero at midlatitudes (−45° magnetic latitude) in a similar way as described by Lomidze et al (). Lomidze et al () found that the recalibration cross‐track ion drift climatology agrees reasonably well in statistical sense with the Weimer () model.…”
Section: Methodsmentioning
confidence: 99%
“…In order to get more usable ion drift data, the recalibration of data was carried out by setting the velocity to zero at midlatitudes (−45° magnetic latitude) in a similar way as described by Lomidze et al (). Lomidze et al () found that the recalibration cross‐track ion drift climatology agrees reasonably well in statistical sense with the Weimer () model. In this study, we primarily focus on the influence of large‐scale FACs on the high‐latitude trough.…”
Section: Methodsmentioning
confidence: 99%
“…We use an updated electric potential model by Edwards (2019), which supplements the database from the Dynamics Explorer-2 spacecraft that was used by Weimer (2005b) with a substantially larger number of measurements from the Swarm spacecraft (Lomidze et al, 2019). Previous models had derived the least-error fit of the model coefficients from electric potentials that were obtained by integrating the measured electric field values along the satellite's path; the latest version fit the coefficients https://doi.org/10.5194/angeo-2020-60 Preprint.…”
Section: The Electric Fieldsmentioning
confidence: 99%